Family Dynamics in Dementia Caregiving: Development and Validation of the Interpersonal Triggers of Guilt in Dementia Caregiving Questionnaire (ITGDCQ). Issue 4 (25th March 2021) - Gallego‐Alberto, Laura; Losada, AndrÉs; MÁrquez‐GonzÁlez, MarÍa; Romero‐Moreno, Rosa; Cabrera, Isabel
Abstract : The objective was to develop the Interpersonal Triggers of Guilt in Dementia Caregiving Questionnaire (ITGDCQ). An emotion frequently experienced by caregivers is guilt. However, the studies analyzing potential factors that generate guilt are scarce. Guilt may be generated through interpersonal interactions. A total of 201 dementia caregivers were evaluated for frequency of leisure, guilt, anxiety, depression, and a pool of items measuring the frequency, and guilt was derived from different behaviors performed by the care recipient (ITGDCQ‐CR) and other relatives (ITGDCQ‐OR). Exploratory factor analysis of the ITGDCQ‐CR showed a two‐factor solution, explaining 56.24% of the variance. The ITGDCQ‐OR subscale also showed two factors, explaining 63.24% of the variance. All the factors had acceptable to good reliability indexes. Positive associations were found between both subscales and depression, anxiety, guilt, and stress associated with CR's behavioral problems. ITGDCQ‐CR was negatively correlated with frequency of leisure. The interpersonal dynamics assessed with the ITGDCQ generated other emotions such as anger or sadness. Through structural equation modeling, 28% of the variance of caregivers' distress was explained by the assessed variables, including a significant contribution of the interpersonal dynamics assessed with the ITGDCQ. The results provide preliminary support for the use of the ITGDCQ as a valid and reliable measure of care recipients' or other relatives' factors that trigger or facilitate the experience of guilt in the caregivers. The association between these factors and caregiver distress suggests potential clinical implications for the findings. Resumen: Objetivo: El objetivo fue desarrollar el Cuestionario sobre los Desencadenantes Interpersonales de Culpa en el Cuidado de Personas con Demencia (Interpersonal Triggers of Guilt in Dementia Caregiving Questionnaire, ITGDCQ). Introducción: Una emoción que generalmente sienten los cuidadores es culpa. Sin embargo, son escasos los estudios que analizan los posibles factores que la generan. La culpa puede generarse mediante las interacciones interpersonales. Métodos: Se evaluó la frecuencia del ocio, la culpa, la ansiedad y la depresión de un total de 201 cuidadores de personas con demencia y se obtuvo un conjunto de ítems que miden la frecuencia y la culpa a partir de diferentes conductas adoptadas por el receptor del cuidado (ITGDCQ‐CR) y otros familiares (ITGDCQ‐OR). Resultados: El análisis factorial confirmatorio del ITGDCQ‐CR mostró una solución de dos factores, lo cual explicó un 56.24 % de la varianza. La subescala de los ITGDCQ‐OR también indicó dos factores, lo cual explica el 63.24 % de la varianza. Todos los factores tuvieron índices de fiabilidad entre aceptables y buenos. Se encontraron asociaciones positivas entre ambas subescalas y la depresión, la ansiedad, la culpa y el estrés asociados con los problemas conductuales del receptor del cuidado. El ITGDCQ‐CR correlacionó negativamente con la frecuencia del esparcimiento. La dinámica interpersonal evaluada con el ITGDCQ generó otras emociones, como ira o tristeza. Mediante los modelos de ecuaciones estructurales, las variables evaluadas explicaron el 28 % de la varianza del malestar de los cuidadores, incluida una contribución significativa de la dinámica interpersonal evaluada con el ITGDCQ. Conclusión: Los resultados ofrecen un respaldo preliminar para el uso del ITGDCQ como medida válida y fiable de los factores de los receptores de cuidado o de otros familiares que desencadenan o facilitan la experiencia de culpa en los cuidadores. La asociación entre estos factores y el distrés de los cuidadores sugiere posibles implicancias clínicas de los resultados. 摘要: 研究目的: 本研究旨在编制《痴呆症患者照料人内疚感的人际诱因调查表（ITGDCQ）。 背景: 照顾者时常会经历的一种情绪是内疚。然而，对产生内疚感的潜在因素进行分析的研究却很少。内疚感可能会在人际交往中产生。 研究方法: 对201名老年痴呆症患者的照料者进行了调查。主要针对他们的休息频率、内疚感、焦虑、抑郁进行评估，并从护理接受者（ITGDCQ‐CR）和其他亲属（ITGDCQ‐OR）的不同行为中得出测量频率和内疚感的项目题库。 研究发现: 对ITGDCQ‐CR进行探索性因素分析，结果显示为双因素解，这解释了56.24%的方差。ITGDCQ‐OR子量表也显示出两个因子，解释了63.24%的方差。各因素的信度指标均能接受或较好。两个子量表与CR的行为问题相关的抑郁、焦虑、内疚和压力之间均有正相关。ITGDCQ‐CR与休息频率呈负相关。用ITGDCQ评估的人际动态产生了其他情绪，如愤怒或悲伤。通过结构方程建模，被评估变量解释了照料者痛苦方差的28%，包括ITGDCQ评估的人际动态的显著贡献。 结论: 研究结果为使用ITGDCQ来评估的人际动态提供了初步支持。研究表明ITGDCQ可以用作一种有效和可靠的测量方法，来测量接受护理的病人的或其他家属方面的因素，这些因素引发或者影响了照顾者的内疚感体验。这些因素与照顾者的痛苦之间的关联性表明这些调查结果可能具有临床意义。